2014
DOI: 10.1002/spp2.1004
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the non‐titanosaurian somphospondylanWintonotitan wattsi(Dinosauria:Sauropoda:Titanosauriformes) from the mid‐CretaceousWintonFormation,Queensland,Australia

Abstract: Wintonotitan wattsi, a Cretaceous titanosauriform sauropod from central Queensland, Australia, is redescribed following a full revision of its osteology. The holotype specimen, a partial postcranial skeleton derived from the lower Upper Cretaceous Winton Formation, comprises axial and appendicular elements. Wintonotitan has been commonly resolved as a non‐titanosaurian somphospondylan titanosauriform since its description, in contrast to its more derived contemporary Diamantinasaurus matildae. We provide a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 95 publications
(299 reference statements)
5
75
2
1
Order By: Relevance
“…The Isisford fossil fauna is dominated by aquatic and semi-aquatic animals, specifically large-bodied, fast-swimming predatory teleost fishes (ichthyodectiforms including Cladocyclus geddesi, and a possible halecomorphan (Faggotter et al 2007;Berrell et al 2014)), as well as small-bodied (< 1.5 m) basal eusuchian crocodyliforms (Isisfordia duncani (Salisbury et al 2006a)). Although smallto medium-size non-avian dinosaurs have also been discovered (but are yet to be described) (Fletcher et al 2009), the remains of larger sauropodan dinosaurs commonly found at other fossil sites within the Winton Formation (see Coombs et al 1981;Molnar 2001;Molnar et al 2005;Salisbury et al 2006b;Hocknull et al 2009;Poropat et al 2015aPoropat et al , 2015b are notably absent, despite over a decade of intense collecting. Also conspicuous by their absence are the remains of dipnoan lungfishes and turtles, which are also found at other Winton Formation fossil sites (see Molnar 1991;Dettmann et al 1992;Kemp 1997).…”
mentioning
confidence: 99%
“…The Isisford fossil fauna is dominated by aquatic and semi-aquatic animals, specifically large-bodied, fast-swimming predatory teleost fishes (ichthyodectiforms including Cladocyclus geddesi, and a possible halecomorphan (Faggotter et al 2007;Berrell et al 2014)), as well as small-bodied (< 1.5 m) basal eusuchian crocodyliforms (Isisfordia duncani (Salisbury et al 2006a)). Although smallto medium-size non-avian dinosaurs have also been discovered (but are yet to be described) (Fletcher et al 2009), the remains of larger sauropodan dinosaurs commonly found at other fossil sites within the Winton Formation (see Coombs et al 1981;Molnar 2001;Molnar et al 2005;Salisbury et al 2006b;Hocknull et al 2009;Poropat et al 2015aPoropat et al , 2015b are notably absent, despite over a decade of intense collecting. Also conspicuous by their absence are the remains of dipnoan lungfishes and turtles, which are also found at other Winton Formation fossil sites (see Molnar 1991;Dettmann et al 1992;Kemp 1997).…”
mentioning
confidence: 99%
“…Generally, the number of elements in the sauropod carpus decreases and appears to culminate in complete absence of ossified elements in titanosaurs (Borsuk-Bialynicka, 1977;Poropat et al, 2015a). Proximal carpals appear to be unossified in early sauropodomorphs and in the basal eusauropod Shunosaurus (Zhang, 1988;Benton et al, 2000;Remes, 2008;Sertich and Loewen, 2010), with the possible exception of the intermedium (e.g., in Jingshanosaurus xinwaensis and Seitaad ruessi; Remes, 2008;Sertich and Loewen, 2010).…”
Section: Manusmentioning
confidence: 99%
“…It has often been hypothesized that the reduction of the sauropod carpus did not lead to only two ossified carpals in Camarasaurus or to the complete absence of carpal elements in certain titanosaurs, but that some of the primordially eleven elements remained cartilaginous during lifetime (Romer, 1956;Janensch, 1961;Borsuk-Bialynicka, 44 1977; Bonnan, 2003;Apesteguía, 2005;Poropat et al, 2015a). Other authors proposed that a thick layer of hyaline cartilage was enclosing the two bony carpals (Jensen, 1988;Wilson and Sereno, 1998).…”
Section: Manusmentioning
confidence: 99%
See 2 more Smart Citations